2008
DOI: 10.1007/s00442-007-0946-1
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of invasive plants in plant–pollinator networks

Abstract: The structural organization of mutualism networks, typified by interspecific positive interactions, is important to maintain community diversity. However, there is little information available about the effect of introduced species on the structure of such networks. We compared uninvaded and invaded ecological communities, to examine how two species of invasive plants with large and showy flowers (Carpobrotus affine acinaciformis and Opuntia stricta) affect the structure of Mediterranean plant-pollinator netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
304
7
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(329 citation statements)
references
References 46 publications
14
304
7
4
Order By: Relevance
“…For example, Lopezaraiza-Mikel et al (2007) could find no suitable un-invaded control sites for comparison with their invaded and experimentally cleared sites. Bartomeus et al (2008b) found similar pollinator community richness in invaded and uninvaded plots, but these were only separated by around 300 m. Hence conclusions about the impacts of the invader on the native community are difficult to draw since it is difficult to measure the true native community. In addition, if displacement of native forage resources causes native specialist bees to disappear, there may be a time-lag during which this loss occurs, which may be difficult to detect via short-term alien removal experiments.…”
Section: Direct Impacts On Beesmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Lopezaraiza-Mikel et al (2007) could find no suitable un-invaded control sites for comparison with their invaded and experimentally cleared sites. Bartomeus et al (2008b) found similar pollinator community richness in invaded and uninvaded plots, but these were only separated by around 300 m. Hence conclusions about the impacts of the invader on the native community are difficult to draw since it is difficult to measure the true native community. In addition, if displacement of native forage resources causes native specialist bees to disappear, there may be a time-lag during which this loss occurs, which may be difficult to detect via short-term alien removal experiments.…”
Section: Direct Impacts On Beesmentioning
confidence: 96%
“…For example, Carpobrotus spp. in California (Aigner, 2004), the Balearic Islands (Moragues and Traveset, 2005), and north-eastern Spain (Bartomeus et al, 2008b) have varying impacts on different taxa of native plants (Tab. I).…”
Section: Indirect Impacts Via Effects On Plant Communitiesmentioning
confidence: 99%
“…In contrast, the model that performed the worst was the competitive model. This demonstrates that I. glandulifera is more likely to add interactions to the community than to remove them (Chittka and Schu¨rkens 2001, Memmott and Waser 2002, Aizen et al 2008, Bartomeus et al 2008). …”
Section: Comparisons With Field Studymentioning
confidence: 96%
“…Although invasive mutualists seem able to alter the 6 E-mail: lrusso@cornell.edu network structure of resident communities, the results of comparative studies are sometimes contradictory. For example, invasive mutualists can increase the nestedness of networks they invade (Bartomeus et al 2008), but decrease connectance among resident species (Aizen et al 2008). Other studies find little or no apparent impact of a species invasion on network structure (e.g., Vila´et al 2009, Carvalheiro et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, facilitative effects on the reproductive success of co-flowering native plants have been reported in the presence of the invasive weed Oxalis pescaprae [150]. Likewise, it has been shown that litter of invasive exotic plants facilitated growth of the dominant native plants by altering soil moisture in Californian shrublands [151]. Additionally, in some cases, the presence of exotic plant species facilitated the visit of pollinators to native species [152].…”
Section: Positive Relationships Between Native and Exotic Species In mentioning
confidence: 99%